Peningkatan Pemahaman dan Partisipasi Pemilih Pemula pada Pemilu 2024 di Desa Sukadadi Kecamatan Gedong Tataan Kabupaten Pesawaran - Farida; Nurul Fadila, Firda; Aliya, Nevi; Arieshanti, Tiara Maysha (Swadaya: Jurnal Pengabdian Masyarakat, 2025)
First-time voters play a crucial role in the success of the 2024 General Election. However, their lack of political understanding and low participation pose challenges to achieving a high-quality democracy. This community service aims to enhance the knowledge and participation of first-time voters in Sukadadi Village, Gedong Tataan District, Pesawaran Regency through the Service Learning method. Activities include election socialization, interactive discussions, and participant comprehension evaluations. The results show a significant increase in political awareness, knowledge, and the willingness of first-time voters to exercise their voting rights in the 2024 election. Thus, political education for first-time voters has proven effective in encouraging active electoral participation and strengthening democratic culture at the local level.